2022
DOI: 10.1155/2022/4801695
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of Shugan Xiaozhi Decoction on Nonalcoholic Fatty Liver Disease via Mediating Gut-Liver Axis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a chronic liver disease with an increasing incidence rate but few therapies. Shugan Xiaozhi decoction (SX) has demonstrated beneficial effects in treating NAFLD with an unclear mechanism. This study was aimed at investigating the therapeutic mechanism of SX on high-fat diet-induced NAFLD rats via the gut-liver axis. Hepatic steatosis and integrity of intestinal mucosa in NAFLD rats were assessed by histopathological staining. The level of lipid and inflammation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…These inconsistent results might be due to different subjects observed in the studies. An animal study revealed that the relative abundance of Ruminococcaceae was elevated in high fat diet-induced NAFLD rats, and a TCM formula called Shugan Xiaozhi decoction exerted beneficial effects in treating NAFLD with decreased abundance of Ruminococcaceae and other gut microbiota ( Yang et al., 2022 ). Interestingly, we also noticed similar results in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These inconsistent results might be due to different subjects observed in the studies. An animal study revealed that the relative abundance of Ruminococcaceae was elevated in high fat diet-induced NAFLD rats, and a TCM formula called Shugan Xiaozhi decoction exerted beneficial effects in treating NAFLD with decreased abundance of Ruminococcaceae and other gut microbiota ( Yang et al., 2022 ). Interestingly, we also noticed similar results in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Shugan Xiaozhi Decoction, a formula that can attenuate NAFLD in high-fat diet-induced rats, can also inhibit the translocation of LPS to avoid inflammation damage and increase ZO-1, occludin to fortify the gut barrier. This effect may be correlated with the lifting levels of f_Prevotellaceae and declining those of f_Desulfovibrionaceae and f_Erysi-Pelotrichaceae ( Yang et al., 2022a ). Mulberry leaf polysaccharide (MLP) can enhance the gene expression of occludin 1, ZO-1 and claudin 5 and relive intestinal villus damages.…”
Section: Tcm Enhance Gut Barrier Via Regulating Gut Microbiotamentioning
confidence: 96%
“…First, PPARα activation can prevent HFD-induced NAFLD steatosis in models by activating the AMPK activation-mediated PPARγ coactivator-1α (PGC-1α) signaling pathway [ 59 ]. In addition, treatment with the Shugan Xiaozhi decoction, a component of artemisiae scopariae herb, significantly suppressed the gut-liver axis in NAFLD models by activating PPAR-mediated lipid metabolism [ 60 ]. Previous studies have indicated that PPARβ/δ shows high metabolic activity, lipid metabolism, glucose homeostasis, and inflammation in hepatocytes, Kupffer cells, and hepatic stellate cells through AMPK activation-mediated suppression of the inflammatory signaling pathway [ 58 ].…”
Section: Inflammatory Signaling Pathways Under Liver Injurymentioning
confidence: 99%